The Factors Affecting Students’ Online Learning Outcomes during the COVID-19 Pandemic: A Bayesian Exploratory Factor Analysis - Pham, Thi Tinh Thuong; Le, Hoang Anh; Do, Doan Trang (Education research international, 2021)
The COVID-19 pandemic, a public health crisis of worldwide importance, announced by the World Health Organization (WHO) in January 2020 as an outbreak, has made distance education through the E-learning system an urgent and irreplaceable requirement. The study assessed factors affecting students’ online learning outcomes during the COVID-19 pandemic through interviews with 404 students who were subjects of the survey using the convenience sampling method via questionnaires. The study utilized the reliability analysis through Cronbach’s Alpha and the Bayesian Exploratory Factor Analysis (BEFA). The evaluation results of the research scales showed that 28 observed variables were used to measure 7 research concepts. Test results of the hypotheses showed that students’ online learning outcomes are affected by 6 factors in the descending order, respectively, learner characteristics, perceived usefulness, course content, course design, ease of use, and faculty capacity.